Engineering strategies and active site identification of MXene-based catalysts for electrochemical conversion reactions - Zhao, Yufei; Zhang, Jinqiang; Guo, Xin; Cao, Xianjun; Wang, Shijian; Liu, Hao; Wang, Guoxiu (Chemical Society Reviews, 2023)
This review summarizes engineering strategies to modify MXene-based catalysts and their active site identification for applications in electrochemical conversion reactions.